Aluminum and toxicity - Gökmen, Sedat; Gül, Burcu (Kastamonu Üniversitesi, 2023)
Aluminum (Al) is the third most prevalent element on earth after oxygen and silicon. Al compounds are used in the production of many different products including pots, pans, paints, varnishes, lubricants, cosmetics, vaccinations, pharmaceuticals, and nano-carrier systems, in the field of veterinary medicine and industry. The toxicity in animals can occur through various routes, including ingestion (food, drinking water), inhalation (air, pharmaceutical, agrochemical), and injection (pharmaceutical, vaccine). Acute poisoning in animals is rare and usually occurs following exposure. Numerous pathological effects have been associated with Al accumulation in mammalian tissues. The accumulation in tissues can Al accumulation in mammalian tissues causes various pathological disorders affecting nervous, immune, skeletal, reproductive system, lungs and breast health. The toxic effects of Al cause oxidative stress, immunological changes, genotoxicity, proinflammatory, peptide denaturation or transformation, enzymatic dysfunction, metabolic dysregulation, amyloidogenesis, membrane disruption, iron dyshomeostasis, apoptosis, necrosis and dysplasia. Al is neurotoxic, increases the permeability of the blood brain barrier and inhibits many important enzymes in the brain. This study aimed to reveal the toxicity of Al, its mechanism of action and its relationship with conditions such as vaccines, cancer, etc. in animals.
Keywords: Veterinary Surgery; Veteriner Cerrahi; Veterinary Pharmacology; Veteriner Farmakoloji